1989
DOI: 10.1161/01.res.65.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation of the area postrema. Permeability and vascular responses.

Abstract: The area postrema is a circumventricular organ that plays an important role in neurohumoral regulation of the circulation. We have developed a method to examine permeability and vascular responses of the microcirculation of the area postrema in vivo. A craniotomy was performed over the dorsal brain stem in anesthetized rats, and blood vessels to the area postrema were visualized with fluorescein microscopy. Extravasation of sodium fluorescein (MW, 386), but not 150 kDa (MW) fluorescein isothiocyanate-dextran, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…However, we cannot completely rule out the possibility of suppression of brain Ang II activity by enalapril since by long-term administration enaJapril can penetrate the circumventricular organs of the brain such as the area postrema, which has a fenestrated blood-brain barrier. 49 Furthermore, our observations, in which the RSNA range and the range of reflex sympathetic excitation of enalapriltreated SHR did not exceed those of untreated WKY rats and the range of reflex bradycardia was increased by enalapril, may have resulted from the agent's exerting a sympathoinhibitory or a vagomimetic action, or both. 50 ' 51 Therefore, enalapril may exert its effect on baroreceptor reflex sensitivity partially via suppression of brain Ang II activity in addition to blood pressure reduction.…”
mentioning
confidence: 59%
“…However, we cannot completely rule out the possibility of suppression of brain Ang II activity by enalapril since by long-term administration enaJapril can penetrate the circumventricular organs of the brain such as the area postrema, which has a fenestrated blood-brain barrier. 49 Furthermore, our observations, in which the RSNA range and the range of reflex sympathetic excitation of enalapriltreated SHR did not exceed those of untreated WKY rats and the range of reflex bradycardia was increased by enalapril, may have resulted from the agent's exerting a sympathoinhibitory or a vagomimetic action, or both. 50 ' 51 Therefore, enalapril may exert its effect on baroreceptor reflex sensitivity partially via suppression of brain Ang II activity in addition to blood pressure reduction.…”
mentioning
confidence: 59%
“…The hypothesis was that, because the blood-brain barrier is absent, circulating humoral stimuli would have pronounced effects on arterioles of the area postrema. 36 To our surprise, intravascular vasopressin did not have selective constrictor effects on arterioles that supply the area postrema. The explanation for these findings became apparent when we observed that the blood-brain barrier, which is absent in capillaries of the area postrema, appears to be present in arterioles to the area postrema.…”
Section: Area Postremamentioning
confidence: 66%
“…The explanation for these findings became apparent when we observed that the blood-brain barrier, which is absent in capillaries of the area postrema, appears to be present in arterioles to the area postrema. 36 Based on these findings, we suggest that, in contrast to the choroid plexus, circulating stimuli such as vasopressin may not have selective effects on blood flow to the area postrema (Figure 2). …”
Section: Area Postremamentioning
confidence: 85%
“…The vasculature of the CVOs is apparently different from the typical BBB vasculature of the brains since the CVOs do not express the tight junction proteins [7][8][9][10][11] , and therefore, blood-derived substances are permeable to the vasculature of the CVOs. [12][13][14] Recently, however, we have shown that vascular permeability of low-molecular-mass tracers is lower in the sensory CVOs as compared with that in the secretory CVOs and the kidney, indicating that vascular permeability of the sensory CVOs is largely restricted. 15 In the sensory CVOs, fenestrated vasculature allows parenchyma cells to sense a wide variety of blood-derived substances and convey their information into other brain regions for the control of autonomic and inflammatory reactions and/or behaviours.…”
Section: Introductionmentioning
confidence: 97%